„Niebo trzecie” księdza Piotra. Szkic komparatystyczny - Fiećko , Jerzy (Przestrzenie Teorii, 2020)
The author analyses the function of the “Third Heaven” motif, which appears at the end of the fifth scene in Mickiewicz’s drama, Forefathers’ Eve Part III - this is where the Angels decide to take the soul of the sleeping priest Peter, one of the main characters in this work, for a short time. The author questions the inspiration that the poet might have drawn from St. Paul’s 2nd Letter to the Corinthians and from the writings of theosophers such as Jakob Boehme (especially Aurora or Rising at Dawn) and Emanuel Swedenborg (his treatise on Heaven and Hell), in which the theme of a “Third Heaven” played an important role. Research has already drawn attention to these relationships. Making a conditional, historically probable assumption that the influence of these works has had a significant impact on the formation of the supernatural world in Mickiewicz’s drama, the author considers the semantic-ideological consequences that would result from placing a monk’s soul in the “Third Heaven” in St. Paul’s, Boehme’s and Swedenborg’s versions, respectively. In conclusion, the author formulates the thesis that greatest number of arguments can be advanced in favour of a connection with Swedenborg’s concept, although this does not settle the matter definitively.